NuSTAR AND INTEGRAL OBSERVATIONS OF A LOW/HARD STATE OF 1E1740.7-2942 - Natalucci, Lorenzo; Tomsick, John A.; Bazzano, Angela; Smith, David M.; Pottschmidt, Katja; et al (IOP Publishing, 2013)
The microquasar 1E1740.7-2942, also known as the "Great Annihilator," was observed by NuSTAR in the summer of 2012. We have analyzed in detail two observations taken ∼2 weeks apart, for which we measure hard and smooth spectra typical of the low/hard state. A few weeks later the source flux declined significantly. Nearly simultaneous coverage by INTEGRAL is available from its Galactic Center monitoring campaign lasting ∼2.5 months. These data probe the hard state spectrum from 1E1740.7-2942 before the flux decline. We find good agreement between the spectra taken with IBIS/ISGRI and NuSTAR, with the measurements being compatible with a change in flux with no spectral variability. We present a detailed analysis of the NuSTAR spectral and timing data and upper limits for reflection of the high energy emission. We show that the high energy spectrum of this X-ray binary is well described by thermal Comptonization.
Authors: - Lorenzo Natalucci, John A. Tomsick, Angela Bazzano, David M. Smith, Matteo Bachetti, Didier Barret, Steven E. Boggs, Finn E. Christensen, William W. Craig, Mariateresa Fiocchi, Felix Fürst, Brian W. Grefenstette, Charles J. Hailey, Fiona A. Harrison, Roman Krivonos, Erik Kuulkers, Jon M. Miller, Katja Pottschmidt, Daniel Stern, Pietro Ubertini, Dominic J. Walton, and William W. Zhang